2017
DOI: 10.1155/2017/3958967
|View full text |Cite
|
Sign up to set email alerts
|

Development of On-Road Exhaust Emission and Fuel Consumption Models for Motorcycles and Application through Traffic Microsimulation

Abstract: This study developed on-road exhaust emission and fuel consumption models for application in traffic microsimulations to estimate motorcycle emissions and fuel consumption in an Asian developing city. The motorcycle onboard measurement system was developed to instantaneously measure and continuously record on-road driving data, including the speed-time profile, exhaust emissions, and fuel consumption per second. The test motorcycle was driven on roads around Khon Kaen City, Thailand, to collect on-road driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Since large volumes of data are obtained, their analysis is important to derive the candidate or representative driving cycle. Driving cycles are constructed by various methods like trip based cycle construction, the micro-trip approach 34,35 (Al-Samari et al 2016), cluster analysis, 3638 the trip segment method, 12 a Markov Chain Monte Carlo simulation for urban mixed roads 13,14,39 (Fries et al, 2018; Li et al 2017) 40,41 , and micro-simulation model 42 (Kumar et al 2012). Trip based and Micro-trip based methods are adapted widely by the researchers in Asian countries.…”
Section: Methods Of Construction Of Driving Cyclementioning
confidence: 99%
“…Since large volumes of data are obtained, their analysis is important to derive the candidate or representative driving cycle. Driving cycles are constructed by various methods like trip based cycle construction, the micro-trip approach 34,35 (Al-Samari et al 2016), cluster analysis, 3638 the trip segment method, 12 a Markov Chain Monte Carlo simulation for urban mixed roads 13,14,39 (Fries et al, 2018; Li et al 2017) 40,41 , and micro-simulation model 42 (Kumar et al 2012). Trip based and Micro-trip based methods are adapted widely by the researchers in Asian countries.…”
Section: Methods Of Construction Of Driving Cyclementioning
confidence: 99%
“…Some participants were even able to reduce their fuel consumption by as much as 15.1%, enforcing the effectiveness and viability of fuel-efficient driving [9]. Other studies specifically focused on reducing the carbon emissions of motorcycles have also shown that simply employing idling-stop requirements on red lights and reducing overall idling time can reduce the fuel consumption of motorcycles by 10-19%, CO2 emissions by 18%, and NOx emissions by 6.7% [10] [11].…”
Section: Eco Ridingmentioning
confidence: 99%
“…In Taiwan, motorcycles represent 67% of all motor vehicles contributing to 38% of all CO emissions [5,6]. In Thailand, some 56% of all registered motor vehicles are motorcycles [11]. Motorcycles comprise the lion's share of vehicles in Bangkok Metropolitan Region (BMR) with some 20 million in number, which are responsible for 19% of total CO emissions [12].…”
Section: Motorcycles In Southeast Asiamentioning
confidence: 99%
“…However, adhering to (7) in the case would mean satisfying the constraints listed below-only these four constraints are active for the given example. 0 + 0 + 01 ≤ 1 (11) 0 + 0 + 01 ≤ 1 (12) 3 + 3 + 34 ≤ 4 (13)…”
Section: The Vrp-el Modelmentioning
confidence: 99%